การประยุกต์ใช้เทคนิคการจำลองสถานการณ์ในการลด ระยะเวลารอของลูกค้าสำหรับธุรกิจคัดแยกขยะรีไซเคิล - สุวัฒน์ บุญเคลือบ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purposes of this study were: 1) to reduce a waiting time of customer, 2) to allocate a sale service provider in recycling waste business. For circumspect consideration and determination, service theories, customer satisfaction, 7 wastes, ECRS techniques, key performance indicator and simulation system were used to be factors for these objectives. The improvement for working process by using arena simulation program is developed 3 new models, which are; 1) reducing the distance of sale man between sale point and cashier from 50 feet to 25 feet reduces the time from 2.5 minutes to 1 min, so that the waiting time of customer is also reduced from 140 minutes to 134 minutes, 2) increasing the sale man from 1 to 3 sale man at the time that the number of customer is high, this model reduces the waiting time of customer from 140 minutes to 13 minutes, 3) assigning 1 sale man only 1 process which reduces the waiting time from 140 minutes to 93 minutes. As the results of the study were as the simulation indicates that the second model can reduces the waiting time of customer effectively which satisfies customer.